Potential for treatment benefit of small molecule CGRP receptor antagonist plus monoclonal antibody in migraine therapy. (19th May 2020) - Mullin, Kathleen; Kudrow, David; Croop, Robert; Lovegren, Meghan; Conway, Charles M.; Coric, Vladimir; Lipton, Richard B.
Abstract : Objective: To provide the first clinical report that 2 calcitonin gene-related peptide (CGRP) therapies, a small molecule CGRP receptor antagonist and an anti-CGRP receptor antibody, can be used concomitantly to treat refractory migraine. Methods: Case reports are presented of 2 patients participating in a long-term safety study of rimegepant 75 mg oral tablets for acute treatment (NCT03266588). After Food and Drug Administration approval of erenumab, both patients started subcutaneous erenumab monthly as allowed per protocol. Results: Patients were women 44 and 36 years of age with ≥2 decades of self-reported suboptimal response to multiple migraine medications. Patient 1 used rimegepant for 6 months and then started erenumab 70 mg subcutaneous monthly. Despite a response to preventive treatment with erenumab, she experienced substantial relief treating 7 of 7 acute attacks with rimegepant and eliminated regular, frequent use of ibuprofen and a caffeinated analgesic. Patient 2 used rimegepant for 60 days before starting erenumab 140 mg subcutaneously monthly. While on erenumab, 9 of 9 attacks treated with rimegepant responded. She stopped near-daily use of injectable ketorolac and diphenhydramine. While using rimegepant alone or together with erenumab, patients reported no related adverse events. Conclusions: Rimegepant 75 mg may be effective for acute treatment during concomitant erenumab preventive administration. The mechanism underlying the benefits of concomitant use of a small molecule CGRP receptor antagonist and an anti-CGRP receptor antibody is unknown and requires further study. ClinicalTrials.gov identifier: NCT03266588. Classification of evidence: This study provides Class IV evidence that for patients with migraine using erenumab, rimegepant is effective for acute treatment.